Engine speed reduction for hydraulic machinery using predictive algorithms. Issue 1 (1st April 2019) - Wiens, Travis
This paper presents an analysis of the potential for engine speed reduction in hydraulic equipment, taking into account not only the minimum engine speed required to meet the current flow demand, but also the minimum speed capable of accelerating the engine to meet increased flow demand in the near future. This is a predictive task, as it requires an estimate of the operator's intention to increase flow demand. We present an analysis of the potential for engine speed reduction using a work cycle from a 40 ton excavator loading a truck, which results in a potential 33% reduction in the mean engine speed with no reduction in useful work rate. We also present two new engine speed control algorithms to perform this predictive task. These controllers are easy to tune and require only a small amount of information about the plant and work cycle. A simulation study is performed that demonstrates the controller's performance and studies the effect of tuning parameters.